Role of dietary habits in menstrual disorders among adolescent girls in Navi Mumbai, Western Maharashtra - Vaishali Talekar; Maharaj Singh; Kalpana Kamble; Dhirajkumar Mane (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: India is a developing country where malnutrition is the most common problems; we are dealing with emerging problems of consumption of convenience food and street food. These foods are easily available, awesome taste, have some packages and advertisements which attracts the new generations and skipping meals starts. Adolescent girls are getting the problems of overweight, underweight, thyroid disorders, anemia, and other hematological disorders. Ultimate aim of this research is to find out an association about between dietary habits and menstrual disorders in adolescent girls. METHODOLOGY: An observational study was carried out in adolescent girls of MGM School, Navi Mumbai, India, from October 2021 to December 2021, to find out the relation between dietary pattern verses menstrual disorders among adolescent girls. Numerical pain scale, modified women's health questionnaire, and daily diary were used to collect data from 100 adolescent girls. Nonprobability purposive sampling technique was used to select adolescent girls. STATISTICAL ANALYSIS: Statistical analysis was done using SPSS 24.0 software. RESULTS: The average age of menarche was 12.9 ± 2.7 years. The study showed that girls experienced moderate menstrual pain (54%), severe menstrual pain (21%), and premenstrual symptoms in 36% of adolescence girls. More than 42% of participants were eating street food and many of the girls had habits of skipping the meals in the afternoon. It was found that there was a significant association between dietary habits and menstrual problems (P ≤ 0.0001). The correlation coefficient between dietary habits and menstrual disorders was identified as r = 0.7 with P < 0.05. CONCLUSION: The menstrual disorders were arising problems among girls of schools of Navi Mumbai. Daily intake of appropriate amount of protein, CHO, fat, vitamins, and minerals can help reduce menstrual problems facing by adolescent girls.